Respuesta :
Answer:
b = 1.25
Step-by-step explanation:
Simplifying
4(b + -6) + 19 = 0
Reorder the terms:
4(-6 + b) + 19 = 0
(-6 * 4 + b * 4) + 19 = 0
(-24 + 4b) + 19 = 0
Reorder the terms:
-24 + 19 + 4b = 0
Combine like terms: -24 + 19 = -5
-5 + 4b = 0
Solving
-5 + 4b = 0
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '5' to each side of the equation.
-5 + 5 + 4b = 0 + 5
Combine like terms: -5 + 5 = 0
0 + 4b = 0 + 5
4b = 0 + 5
Combine like terms: 0 + 5 = 5
4b = 5
Divide each side by '4'.
b = 1.25
Simplifying
b = 1.25
Answer:
Step-by-step explanation:
1. mulitply 4 and b and than mulitply 4 and 6
2. subtract 24 from both sides.
3. divied 4 from both sides
4. get your anwser